Advances in group processes. vol. 39 - Kalkhoff, Will; Thye, Shane R.; Lawler, Edward J. (Advances in group processes ;, 2022)
Advances in Group Processes publishes theoretical analyses, reviews, and theory based empirical chapters on group phenomena. The series adopts a broad conception of "group processes." This includes work on groups ranging from the very small to the very large, and on classic and contemporary topics such as status, power, trust, justice, social influence, identity, decision-making, intergroup relations, and social networks. Previous contributors have included scholars from diverse fields including sociology, psychology, political science, economics, business, philosophy, computer science, mathematics, and organizational behavior. Volume 39 brings together papers related to a variety of topics in small groups and organizational research. The volume includes papers that address theoretical and empirical issues related to gendered group processes as well as to the role of networks and exchange in creating fairness perceptions, legitimacy, and reactions to identity non-verification. In addition, several papers advance research on social inequalities by offering theoretical and methodological contributions concerning status processes, discussion group methods, and the use of neuroimaging to study reactions to racism and systemic exclusion. Overall, the volume includes papers that reflect a wide range of theoretical approaches from leading scholars who work in the general area of group processes.